The relationship between critical power and running performance - Kolbe, T.; Dennis, S. C.; Selley, E.; Noakes, T. D.; Lambert, M. I. (Journal of Sports Sciences, 1995)
Critical power is a theoretical concept that presumes there is a certain work-rate which may be maintained without exhaustion. The extent to which critical power predicts running performance over varying distances has not been determined, and so the aim of this study was to correlate measurements of critical power in the laboratory to running performances in the field at 40 m and 1, 10 and 21.1 km in a group of .17 male long-distance runners (mean +/- S.D. age = 31.7 +/- 7.3 years). Each subject ran to exhaustion on the treadmill in the laboratory at six different speeds, ranging from 17 to 25 km h-1. Least squares analyses were used to fit an exponential decay to the relationship between the running speed (y) versus time to exhaustion (x). Critical power was calculated as the running speed (y) coinciding with the asymptote or C parameter of the y = A.e(-Bx) + C relationship. The VO2 max was also measured in all subjects. For the data in the field, each subject was timed over 40 m and 1 km and participated in 10- and 21.1-km races. The mean critical power of the subjects in this study was 18.5 +/- 1.6 km h-1. The test-retest correlation coefficient for the determination of critical power was r = 0.99. The mean VO2 max, measured in a progressive exercise protocol starting at 13 km h-1 and increasing by 1 km h-1 every minute, was 59.2 +/- 4.6 ml O2 kg-1 min-1.